Transcriptome Sequencing Reveals Key Genes in Three Early Phases of Osteogenic, Adipogenic, and Chondrogenic Differentiation of Bone Marrow Mesenchymal Stem Cells in Rats - Liu, Fanxiao; Dong, Jun; Zhang, Peng; Zhou, Dongsheng; Zhang, Qingyu (Frontiers in Molecular Biosciences, 2022)
Bone mesenchymal stem cells (BMSCs) of multi-directional differentiation and reproductive activity are attractive candidates for bone and cartilage repair. However, the molecular mechanisms underlying the early phase of osteogenesis, adipogenesis, and chondrogenesis of BMSCs are still far from understood. In the current study, BMSCs are isolated from rats, and the gene expression during the initiation of differentiation (phase I), lineage acquisition (phase II), and early lineage progression (phase III) of three-directional differentiation of BMSCs were detected by using high throughput sequencing. Then 356, 540, and 299 differentially expressed genes (DEGs) were identified in phases I, II, and III of osteogenesis, respectively. The numbers are 507, 287, and 428 for adipogenesis, respectively; 412, 336, and 513 for chondrogenesis, respectively. Time-dependent expression patterns of genes were also validated during three-directional differentiation in BMSCs. Hub genes including Ccna2, Cdc20 and Il6 may act as common participants in initiating osteogenesis, adipogenesis and chondrogenesis. Mex3b, Sertad1, and Hopx showed enhanced expression throughout three early phases during the osteogenic differentiation but no significant change in other two-directional differentiation. A similar pattern of Dtx4 and Ibsp expression occurred in adipogenesis and chondrogenesis, respectively. Our findings will help understand the underlying mechanism determining the differentiation fate of BMSCs and provide theoretical support for the clinical treatment of osteoporosis, osteoarthritis, and other age-related bone diseases.